Vaccine hesitancy and Web 2.0: Exploring how attitudes and beliefs about influenza vaccination are exchanged in online threaded user comments - Meyer, Samantha B.; Violette, Richard; Aggarwal, Reenika; Simeoni, Michelle; MacDougall, Heather; Waite, Nancy (Vaccine, 2019)
•The CBC forum provides a space for users to reinforce their pre-existing beliefs.•Rhetorical devices and tactics noted in user exchanges reinforces existing polarization.•Public health engagement may further reduce rejecter's intention to vaccinate. The growth of Web 2.0 has been particularly impactful in shaping information assessment in decision-making with regards to vaccination. The aim of the present study was to explore how attitudes and beliefs about influenza vaccination are exchanged in Web 2.0 through an analysis of user comment threads in response to related news reports on the Canadian Broadcasting Corporation national news website (average of 5.8 million unique visitors per month). User comments (n = 2042) were extracted using a Google Chrome data mining extension, from 33 articles reporting on the seasonal influenza vaccine between September 2015 and October 2016. User comments were analyzed using thematic discourse analysis to identify themes within the data, and also identify how information is exchanged, including identifying the rhetorical devices and tactics used. Mostly unrelated to article content, user comments were extremely polarized with only those with strong positions at either end of the vaccination spectrum (for or against) engaging actively in online debates. Observed exchanges, and the use of rhetorical devices and tactics employed by users are identified as furthering or reinforcing polarization. In addition to exchanging information, forums served as ‘echo chambers’ where individuals connect with likeminded users and collect additional information to reinforce pre-existing beliefs, rather than encouraging the enrichment of user knowledge. Our data lead us to question existing calls for public health engagement in such online forums, as doing so may actually reduce the intention to vaccinate among individuals against vaccination. Rather, we identify a greater need to observe online platforms to better understand the social mechanisms that may contribute to, or reinforce, attitudes and beliefs related to influenza vaccine refusal. Further research may also explore the effect that such dialogue has on the attitudes and beliefs of passively observing individuals who have yet to decide whether to receive the flu vaccine.